KARAKTERISASI BIOPOLIMER DAN EDIBLE FILM DAUN BUNGA SEPATU (Hibiscus rosa-sinensis) DENGAN SORBITOL SEBAGAI PLASTICIZER - , SILMI AULIA FATHARANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Hibiscus rosa-sinensis is a common found plant which leaves arewell known to contain a polysaccharide biopolymer in the form of mucus. Polysaccharide biopolymer is one of component in the manufacture of edible film. Until now, there has been no research on edible biopolymer films from hibiscus leaves. The purpose of this study is to identify the chemical characteristics of (moisture content, ash, methoxyl, proteins, fats and carbohydrates), physical characteristics such as (thickness, tensile strength (tensile strength), elongation (elongation), solubility) and barrier properties (water vapor permeability) edible film produced by isolat biopolymer hibiscus leaves with the addition of sorbitol as a plasticizer. For the making process of biopolymer from hibiscus leaf, it needs to extract the hibiscus leaf by using water, then carried precipitation with ethanol 96%, and continued with drying, and milling. Edible films which made in this study are using a vary concentration of biopolymers isolates 1%, 1.25%, and 1.5% w / v, with a fixed concentration of plasticizer sorbitol, which is 30% w / w isolates biopolymers. The results showed that the yield of isolates biopolymers hibiscus leaf is at 4.17% (w / w). Isolates biopolymer contains 5.11% methoxyl, 11.70% ash, 9.13% moisture, 18.99% protein, 0.96% fat, and carbohydrate (by difference) of 58.68%.In the reducing sugar test showed no detection of biopolymers isolates indicated by the absence of sediment and discoloration. The physical characteristics and barrier properties of edible film show that the higher the concentration of biopolymers isolates will increase the thickness, solubility and tensile strength, but decrease elongation and permeability to water vapor. At the highest concentration of biopolymers isolates were being used, ie 1.5% (w / v), the edible film has 0.09 mm thickness, tensile strength of 4.82 MPa, 73, 80% solubility, 0, 09% elongation , and water vapor permeability 17,43 g.mm/m2 day kPa.